KADER POSYANDU DALAM PEMBUATAN MP-ASI BERBASIS PANGAN LOKAL DI DESA PADANGLAMPE KABUPATEN PANGKEP - Septiyanti Septiyanti; Sartika Sartika (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
The period from infancy in the womb to the first few years of birth is known as the Golden Age, which is a golden period in growth and development in human life. The Golden age is also known as a critical time which, if not used properly, will cause permanent damage. Nutritional intake has an important role in the Golden Age period. Not fulfilling adequate nutritional intake at this time will greatly affect the growth and development of children. The provision of complementary food for ASI (MP-ASI) is one of the factors that can influence this growth and development. Given the importance of nutritional intake during this golden period of child development, it is necessary to provide complementary feeding education to mothers. As the smallest and foremost structure in government health services, posyandu cadres are expected to be able to empower mothers to pay attention to children's health, especially in providing MP-ASI. This community service was carried out with the target of posyandu cadres in Padanglampe Village, Pangkep Regency, South Sulawesi. This community service activity uses an action research approach. This activity succeeded in increasing the knowledge and attitudes of the cadres which were measured using questions before and after the intervention. Sustainability coaching is needed for cadres in order to obtain updated knowledge and skills, especially those related to balanced nutrition, so that they have sufficient provisions in empowering family nutrition.